2017
DOI: 10.1371/journal.pone.0181955
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty in opioid dependency – Relationship with trait anxiety and impulsivity

Abstract: Intolerance of uncertainty (IU) is the tendency to interpret ambiguous situations as threatening and having negative consequences, resulting in feelings of distress and anxiety. IU has been linked to a number of anxiety disorders, and anxiety felt in the face of uncertainty may result in maladaptive behaviors such as impulsive decision making. Although there is strong evidence that anxiety and impulsivity are risk factors for addiction, there is a paucity of research examining the role of IU in this disorder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 68 publications
(69 reference statements)
2
16
1
1
Order By: Relevance
“…As expected, patients were also found to have greater IU than controls ( Table 1 ), which is consistent with past research ( Carleton, Norton & Asmundson, 2007 ; Nelson et al, 2016 ; Garami et al, 2017 ). However, neither of the two indicators of place preference (i.e., the first room entered and the room participants spent more time in during the post-training) was related to IU.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, patients were also found to have greater IU than controls ( Table 1 ), which is consistent with past research ( Carleton, Norton & Asmundson, 2007 ; Nelson et al, 2016 ; Garami et al, 2017 ). However, neither of the two indicators of place preference (i.e., the first room entered and the room participants spent more time in during the post-training) was related to IU.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the current study adopted the CPP task of Radell et al (2016) to compare the potential behavioral effects of IU between individuals undergoing treatment for OUD and healthy controls. First, consistent with prior studies ( Carleton, Norton & Asmundson, 2007 ; Garami et al, 2017 ), we hypothesized that patients would report higher IU than controls. Second, we hypothesized that if patients have reduced reward sensitivity to non-drug reward, they would show reduced preference for the context associated with reward relative to controls.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Using a former version of the test, Kirby et al [39] also found that patients addicted to heroin were more impulsive than healthy controls. The results of other studies that applied different psychological tests showed increased impulsivity in OD patients [14, 18, 40-43]. In heroin users, impulsiveness seems to be higher than in users of prescription opioids only [44].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired impulse control can be a risk factor for drug misuse [15-18]. For example, a lack of control concerning dose and frequency of drug intake might result in overdoses and relapses.…”
Section: Introductionmentioning
confidence: 99%